Semiotic analysis of the representation of the sinister in the feature film «Hereditary» (2018): Carlos Pineda - Pineda, Carlos (Quórum Académico, 2024)
The purpose of this article is to analyze the cinematic and filmic codes that underpin the representation of the sinister in the film «Hereditary» (2018). To this end, a theoretical framework based on the theories of renowned semiologists such as Roland Barthes (1982), Algirdas Julien Greimas (1983), and Umberto Eco (1988) is established. The methodology used in this study is qualitative, with a phenomenological and hermeneutic approach. The technique used was observation and content analysis applied to a corpus composed of the film "«Hereditary»" (2018). As the main finding, it was possible to determine, through the identification and analysis of cinematic and filmic codes, how the atmosphere of the sinister is constructed in this film